2023
DOI: 10.3389/fpubh.2023.1144942
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality and nutrient density in pregnant women according to adherence to Mediterranean diet

Abstract: Background and aimsThe dietary pattern followed during pregnancy, specifically healthy dietary patterns such as the Mediterranean diet, is a key factor in the mother’s and the offspring’s health. Pregnant women dietary intake is not enough to cover the micronutrient requirements of pregnancy, and higher adherence to the Mediterranean diet may improve dietary quality and nutritional density. The aim of the present study was to describe the dietary nutrient intake and diet quality during pregnancy and to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…While there is current interest for adjuvant therapies to improve reproductive outcomes, such as micronutrient supplementation, in the context of assisted reproductive treatments, it has been reported that the best strategy for improving reproductive outcomes is adherence to the Mediterranean diet [57,58]. Part of this effect may be due to the fact that this diet is associated with higher concentrations of micronutrients [57]. In addition, the use of dehydroepiandrosterone, co-enzyme Q10, melatonin, and essential fatty acids may be beneficial in some situations [58].…”
Section: Discussionmentioning
confidence: 99%
“…While there is current interest for adjuvant therapies to improve reproductive outcomes, such as micronutrient supplementation, in the context of assisted reproductive treatments, it has been reported that the best strategy for improving reproductive outcomes is adherence to the Mediterranean diet [57,58]. Part of this effect may be due to the fact that this diet is associated with higher concentrations of micronutrients [57]. In addition, the use of dehydroepiandrosterone, co-enzyme Q10, melatonin, and essential fatty acids may be beneficial in some situations [58].…”
Section: Discussionmentioning
confidence: 99%
“…LA is a typical polyunsaturated fatty acid (PUFA) in plant-derived oils, mainly derived from vegetable oils and nuts in the diet [ 163 ]. A diet high in linoleic acid is typical of the Mediterranean diet, and previous studies have suggested that in patients with DKD, adopting the Mediterranean diet could potentially present a lifestyle approach that effectively postpones kidney deterioration [ 164 , 165 ]. A study conducted on 366 patients as part of a clinical trial revealed that an enhanced intake of polyunsaturated fatty acids had a notable association with a decreased preponderance of DKD [ 166 ].…”
Section: The Role Of Gut Microecological Interventions In Retarding T...mentioning
confidence: 99%